Effectiveness of aid for trade in small and vulnerable economies an empirical assessment - Calì, Massimiliano (London commonwealth secretariat, 2011)
This Economic Paper presents the first analyses of the use and effectiveness of Aid for Trade (AfT), the initiative to help developing countries boost their involvement in the global economy, for small and vulnerable economies (SVEs). It examines in detail the extent to which SVEs have been able to access AfT funds and to what extent this assistance has helped them to improve their trade performance.
Includes bibliographical references (pages 57-59).
Keywords: Economic assistance--Developing countries